Five forces that change everything how technology is shaping our future - Hoffman, Steven S. (Matt Holt Books, an imprint of BenBella Books, Inc., 2021)
This book takes you on a journey to see what the most brilliant minds of our age are dreaming up. It reveals how new scientific breakthroughs and business ventures are poised to reshape our lives"--